Exploring Filipino Kindergartens’ Perspective on Disasters: A Descriptive Case Study - Legaspino, Liza Cordero; Varela, Leonora Parungao (Southeast Asia Early Childhood Journal, 2023)
Disasters continue to have adverse effects around the globe leaving many lives susceptible to hazards and fatalities most especially children. The Philippines, known to be one of the most disaster-prone countries in the world, experiences earthquakes, typhoons, and flooding yearly. For the reason of the country’s vulnerability to disasters, it is expected that both adults and children can demonstrate preparedness to such disasters.  Hence, in order to improve the disaster preparedness of kindergarten pupils, we must begin looking at their perspectives before conceptualizing kindergarten lessons about disasters. This study focused on Filipino Kindergarten’s perspectives on disasters. This study sought to; (i) describe children’s perspectives on disasters; and (ii) determine significant concepts that can be used for School Disaster Risk Reduction Management specifically for kindergarten. The cases were kindergarten pupils from different public schools residing in Metro Manila. There were nine (9) cases, three Kindergartens per specific type of disaster experienced, whether earthquake, flooding, or typhoon. Based on the findings of the study, children have perspectives to which their capacity to express their knowledge, feelings, plans, actions on disasters are manifested. Children also have the competence to think of other’s welfare in the event of disasters and are interested to learn more about disasters as they have suggested ways in which they can enjoy learning about Disaster Risk Reduction (DRR).